Hasil Belajar Peserta Didik Kelas X SMAN 38 Jakarta Setelah Menggunakan Buku Saku Digital - Ramdhana, Surya Dinar; Asma Irma Setianingsih; Lia Kusumawati (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2025)
The purpose of this study was to determine the differences in learning outcomes of tenth-grade students at SMAN 38 Jakarta on the topic of the atmosphere after using the BMKG Digital Climatology Pocket Book. This research is a quantitative study using an experimental approach. The design of this research is a quasi-experimental with a nonequivalent control group. The selection of the sample used Purposive Sampling Homogen. Class X6 serves as the experimental group that is given the treatment of the BMKG Digital Pocket Book on Climatology. Meanwhile, Class X5 acts as the control group. The instruments were declared valid and reliable, and the data was found to be normal and homogeneous. The average pre-test score for the experimental class is 56.00, and the post-test score is 87.00. Meanwhile, the average pre-test score for the control class is 56.14, and the post-test score is 81.00. Based on the data analysis results, there is a significant difference in learning outcomes for the experimental class participants, which is 31,00, compared to the control class, which is only 24.86. The percentage increase in scores for the experimental class was 55.35%, while the percentage increase in scores for the control class was only 44.28%.. Therefore, there are differences in the learning outcomes of class X students at SMAN 38 Jakarta on atmospheric material after using the BMKG Climatology Digital Pocket Book.